About Resilience in the Multidimensional Vulnerability Index (MVI) - Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2022)
Origin of the concept related to vulnerability. Before recently invading the vocabulary of the social sciences, the concept of resilience was a physical notion that referred to shock resistance. The use that is now made of it in the social sciences, particularly in economics, psychology, and ecology, remains in accordance with the initial definition: it is a capacity to resist shock or trauma. In the vocabulary of economics the concept of resilience has spread in the wake of that of vulnerability: vulnerability to a shock.
Keywords: 330